2017
DOI: 10.1063/1.4995964
|View full text |Cite
|
Sign up to set email alerts
|

Actuation of a lean-premixed flame by diffuse non-equilibrium nanosecond-pulsed plasma at atmospheric pressure

Abstract: This study investigates the effect of diffuse non-equilibrium nanosecond-pulsed plasma at atmospheric pressure on a lean-premixed CH4-air flame (ϕ = 0.65, P ∼ 0.3 kW). The domain of diffuse plasma existence is explored for both the case of the cold flow (no flame) and the case where a flame is stabilized downstream. The dynamics of plasma propagation and the flame displacement, following a high-voltage pulse, were measured using intensified charge-coupled device imaging. The energy of the plasma was measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…The plasma source is capable of operating in the diffuse and filamentary regime as reported in previous studies with similar conditions [26,[32][33][34]. Qualitatively, for high values of T i , the discharge operates in a hybrid regime with a well defined filament in the center of the plasma and a volume of diffuse glow.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The plasma source is capable of operating in the diffuse and filamentary regime as reported in previous studies with similar conditions [26,[32][33][34]. Qualitatively, for high values of T i , the discharge operates in a hybrid regime with a well defined filament in the center of the plasma and a volume of diffuse glow.…”
Section: Resultssupporting
confidence: 54%
“…On the contrary, higher ν causes a less-stable diffuse regime and the discharge typically turns into a bright spark. Evans et al [34] reported that there is a limit in the amount of discharge events per volume of gas treated before the discharge transits to a spark. As ν increases, more discharge events happen for the same gas volume when the flow rate is kept constant, thus explaining this behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal effect is restricted by limiting the current in the discharge channel, either by a dielectric barrier or by ending the pulse. However, due to the challenges of temperature measurements in plasma-assisted combustion environment, a small thermal effect cannot be completely ruled out [154,192].…”
Section: Chemical Effectmentioning
confidence: 99%
“…Stange et al [19] observed that an AC dielectric barrier discharge (DBD) in the microdischarge mode applied to the fuel flow in a coaxial air-propane nonpremixed flame configuration would cause a flame speed increase, but the authors did not provide details into the potential mechanisms enabling the interaction. More recent work by Elkholy et al [20] and Evans et al [21] apply nanosecond pulsed plasma upstream of lean, premixed methane air flames, with the former using a DBD configuration and the latter a pin-to-pin configuration, and also observe flame speed increase. Typical per-pulse energies used were O(100µJ) and the pulse repetition frequencies up to 10kHz, for actuation on flames with power O(100W ).…”
Section: Introductionmentioning
confidence: 99%